2001
DOI: 10.1080/09687680110033774
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C transport systems of mammalian cells

Abstract: Vitamin C is essential for many enzymatic reactions and also acts as a free radical scavenger. Specific non-overlapping transport proteins mediate the transport of the oxidized form of vitamin C, dehydroascorbic acid, and the reduced form, L-ascorbic acid, across biological membranes. Dehydroascorbic acid uptake is via the facilitated-diffusion glucose transporters, GLUT 1, 3 and 4, but under physiological conditions these transporters are unlikely to play a major role in the uptake of vitamin C due to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(123 citation statements)
references
References 34 publications
5
117
0
1
Order By: Relevance
“…1) as a positron-labeled analog of ascorbic acid for studying oxidative damages in vivo by positron emission tomography (PET). Tissue distribution studies in normal rats or tumor-bearing mice demonstrated that the uptake and distribution pattern of 18 F-DFA has a remarkable resemblance to that reported for [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]ascorbate, with preferential uptake in the adrenal glands and slow brain uptake kinetics. [3][4][5] Recently, Monnier et al used DFA for studying the mechanism in experimental diabetes with 19 F-NMR spectroscopy, showing that DFA is a very powerful tool for the clarification of ascorbate homeostasis and catabolism in vivo.…”
Section: F]fluoro-l-ascorbic Acid (mentioning
confidence: 56%
“…1) as a positron-labeled analog of ascorbic acid for studying oxidative damages in vivo by positron emission tomography (PET). Tissue distribution studies in normal rats or tumor-bearing mice demonstrated that the uptake and distribution pattern of 18 F-DFA has a remarkable resemblance to that reported for [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]ascorbate, with preferential uptake in the adrenal glands and slow brain uptake kinetics. [3][4][5] Recently, Monnier et al used DFA for studying the mechanism in experimental diabetes with 19 F-NMR spectroscopy, showing that DFA is a very powerful tool for the clarification of ascorbate homeostasis and catabolism in vivo.…”
Section: F]fluoro-l-ascorbic Acid (mentioning
confidence: 56%
“…51 This transporter provides high ascorbate concentration in most tissues. In the CNS, ascorbate has several functions including antioxidant protection, peptide amidation, myelin formation, synaptic potentiation and protection against glutamate toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…DHA is maintained at much lower intracellular concentrations than Vitamin C, but has a number of unique properties that set it apart. While the Na þ -dependent cotransporters SVCT1 and SVCT2 transport Vitamin C, DHA is transported by facilitated diffusion via the glucose transporters GLUT1, GLUT2, and GLUT4, with rapid reduction of DHA to Vitamin C occurring within the cell (22). The transport, and structural properties of DHA make it an excellent candidate for in vivo metabolic studies using hyperpolarized 13 C MRSI.…”
Section: Mri | Molecular Imaging | Probe | Kineticsmentioning
confidence: 99%